The Effect of Remedial Learning and Enrichment on Student Learning Outcomes in Fiqh at Madrasah Aliyah - Mardianti Diantama (Nalar: Journal of Pedagogy and Society, 2020)
The purpose of this study was to see if there was an effect of remedial learning and enrichment on fiqh subjects at Madarasah Aliyah in Tualang District, Siak Regency. This research was conducted in Madrasah Aliyah in Tualang District. The sampling technique used purposive sampling as many as 109 students. The results of the analysis show the value of R2 (coefficient of determination) or R Square of 0.750 or 75.0%. This value can be interpreted that the change in student learning outcomes by changes in the value of the remedial and enrichment learning variables is 75.0% while 25% is determined by changes in other factors that are not in the model. The calculated t value for the remedial learning variable (X1) is 10,615 and for the enrichment learning variable (X2) is 15,023. The value of t table for n = 109 with degrees of freedom n-k-1 = 106 and a confidence level of 5% or alpha 0.05 is 1.982. So it can be concluded that remedial and enrichment learning variables have a significant effect on student learning outcomes.